Penyuluhan Sistem Integrasi Tanaman-Ikan, Pemasaran Hasil Pertanian, dan Motivasi Kerja untuk Meningkatkan Pendapatan Petani di Desa Tambaksari Kidul: Extension of Plant-Fish Integration System, Agricultural Product Marketing, and Work Motivation to Increase Farmer Income in Tambaksari Kidul Village - Nugraha, Fadhil Adi; Utami, Pujiati; Adella, Shinta; Anggara, Bayu; Apriliani, Dwi Wahyu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Kembaran District in Banyumas Regency is a rapidly developing residential area that maintains agricultural regions, including Tambaksari Kidul Village. This village has high agrarian potential, fertile soil, and a yearly stable water supply. Local farmers are members of the "Tani Maju" Farmer Group and cultivate secondary crops, vegetables, and freshwater fish. However, challenges such as high fertilizer prices, dependence on inorganic fertilizers, low skills in the plant-fish integration system (PFIS), lack of marketing knowledge, and low work motivation hinder the improvement of farmer welfare. This community service activity aims to improve farmers' knowledge and skills by extending PFIS, agricultural products marketing, and motivation enhancement. The methods used include lectures, focus group discussions, and evaluation through pretest and posttest questionnaires. The community service was conducted at the Tambaksari Kidul Village Hall on Monday, April 28, 2025. Based on the pretest and posttest results, farmers' knowledge regarding the plant-fish integration system, agricultural product marketing, and work motivation increased. Overall, the level of expertise is in the moderate category.